2016
DOI: 10.1371/journal.pone.0156318
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of NMR Based Serum Metabolomic Profiling to Animal Health Monitoring: A Case Study on Iron Storage Disease in Captive Sumatran Rhinoceros (Dicerorhinus sumatrensis)

Abstract: A variety of wildlife species maintained in captivity are susceptible to iron storage disease (ISD), or hemochromatosis, a disease resulting from the deposition of excess iron into insoluble iron clusters in soft tissue. Sumatran rhinoceros (Dicerorhinus sumatrensis) is one of the rhinoceros species that has evolutionarily adapted to a low-iron diet and is susceptible to iron overload. Hemosiderosis is reported at necropsy in many African black and Sumatran rhinoceroses but only a small number of animals repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…They also tend to be elevated in the fecal metabolome of obese humans (Patil et al, 2012; Ríos-Covián et al, 2016). It has already been demonstrated that the serum metabolic profile of Sumatran rhinoceroses with symptomatic hemochromatosis differs from that of healthy individuals (Watanabe et al, 2016). However, it is not known if such changes occur as a precursor to or an effect of illness.…”
Section: Introductionmentioning
confidence: 99%
“…They also tend to be elevated in the fecal metabolome of obese humans (Patil et al, 2012; Ríos-Covián et al, 2016). It has already been demonstrated that the serum metabolic profile of Sumatran rhinoceroses with symptomatic hemochromatosis differs from that of healthy individuals (Watanabe et al, 2016). However, it is not known if such changes occur as a precursor to or an effect of illness.…”
Section: Introductionmentioning
confidence: 99%
“…Because the biochemicals typically detected through metabolomic analyses are involved in primary metabolism, this tool can be applied to myriad animal species. Metabolomics has recently been used to assess health status in captive Sumatran rhinoceros (Watanabe, Roth, Bauer, Lane, & Romick‐Rosendale, ), impact of dietary fluctuations in captive common marmosets (Banton et al, ), and toxic effects of contaminants in fish species (Ekman et al, ; Xu et al, ). Metabolomics is used to study the metabolic changes occurring in an organism in response to environmental change and has potential to improve understanding of the stress‐induced changes both in vertebrates and invertebrates, aquatic and terrestrial species, and in response both to natural fluctuations in the environment and disturbances caused by human activities.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic differences in other taxa have been reported at the species level between naked mole rats and mice 11 , and at the breed level in pigs 12 , cattle 13 , chickens 14 , and dogs 15 . However, there is limited information on serum metabolome of rhinos 16 .…”
Section: Introductionmentioning
confidence: 99%